Pengaruh Pemberian Metode Neuro Developmenta Treatment Terhadap Perkembangan Motorik Kasar Pada Anak Penderita Gangguan Akibat Kekurangan Iodium - Darmoko, Dicky Hartyan, Isnaini Herawati, SSt. FT, M. Sc, Agus Widodo, S.Fis, M.Kes (2015)
Supervised By: Isnaini Herawati, S.Fis, M.Sc dan Agus Widodo, S.Fis, M.Fis). Background: According to the World Health Organization (WHO, 2007), disorders caused by iodine deficiency hereinafter abbreviated as IDD, is still a public health problem in 84 developed and developing countries, including Indonesia. One of the consequences of iodine deficiency in children under five, namely the decline in gross motor function. In this case, physiotherapy plays a role in the increase in gross motor skills that children with IDD can move normally. Physiotherapy has several methods of therapeutic approaches used to treat cases of delays in motor development in children, one of them neuro developmental treatment or shortened to NDT. NDT is a therapeutic technique that is specifically aimed at dealing with central nervous system disorders in infants and children, which was developed by Karel and Bertha Bobath in 1967. NDT adheres to two basic principles, namely: (1) the normalization of abnormal tone by bringing to normal movement patterns and exploration of movement, (2) facilitation of normal movement patterns in everyday life. Objective: This study aims to determine the effect of neuro developmental treatment methods for gross motor development in children with iodine deficiency disorders. Methods: This study was an experimental study with a qualitative approach, the method used is the method of one group pre - post test. The number of samples in this study is 3 persons. Result: From the research there is increasing each subject before and after treatment. On the subject of A, the highest increase in the dimensions of crawl that is equal to 13 points. On the subject B, the highest increase in the dimensions stand is 28 points. While the subject C, the highest increase in dimensions crawling at 14 points. All subjects were assessed using GMFM scores. From the analysis of the data showed that the method of treatment of neuro devopmental influence on gross motor development of children with iodine deficiency disorders. Conclusions: The existence of the effect of neuro developmental treatment methods for children with iodine deficiency disorders by using experimental research through qualitative methods. Keyword: Neuro Developmental Treatment, Motor Rough, iodine deficiency and Developmental Disorders.